2014
DOI: 10.4028/www.scientific.net/amm.592-594.1601
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Heat Transfer Enhancement in Pool Boiling by Using 2-Ethyl 1-Hexanol an Additive

Abstract: The addition of additives to the water is known to enhance boiling heat transfer. In the present investigation, boiling heat transfer coefficients are measured for Nichrome wire, immersed in saturated water with & without additive. An additive used is 2-Ethyl 1-Hexanol with varying concentrations in the range of 10-10000 ppm. Extensive experimentation of pool boiling is carried out above the critical heat flux. Boiling behavior i.e. bubble dynamics are observed at higher heat flux for nucleate boiling of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Gajghate S.S. et al [11] work showed that a small amount of 2 ethyl 1 hexanol additive makes the nucleate boiling heat transfer coefficient considerably much higher and that there was an optimum additive (500-1000 ppm) concentration for higher heat fluxes. A most appropriate level of enhancement was observed up to a certain amount of additive 500-1000 ppm in the tested range.…”
Section: Introductionmentioning
confidence: 99%
“…Gajghate S.S. et al [11] work showed that a small amount of 2 ethyl 1 hexanol additive makes the nucleate boiling heat transfer coefficient considerably much higher and that there was an optimum additive (500-1000 ppm) concentration for higher heat fluxes. A most appropriate level of enhancement was observed up to a certain amount of additive 500-1000 ppm in the tested range.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactant additive changes the boiling phenomenon drastically. The addition of very small amounts of surfactant additive in water can enhance nucleate boiling heat transfer remarkably with nichrome wire as plain heater [1][2][3][4][5]. Das et al [6] investigated pool boiling in water -Al 2 O 3 Nanofluid on rectangular stainless steel vessel experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of surface roughness on nucleate boiling heat transfer was studied [46]. Boiling performance of aqueous ammonium chloride as an additive using a nichrome wire heater was experimentally studied [47]. The nucleate boiling heat transfer of gas saturated FC-72 on micro pin finned surface under microgravity was investigated [48].…”
Section: Refrigerants and Dielectric Fluidsmentioning
confidence: 99%